Anti-corruption policy of the European Union: stages of formation, achievements and prospects - Knysh, Serhiy (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article presents the results of a study of the EU experience in the field of fighting corruption at different stages and determines the prospects of the EU anti-corruption policy. The author analyzes the essence of the concept of «corruption" in the legal field of the European Union and its evolution since the founding of the Union in 1992. The peculiarities of regulating various aspects of anti-corruption policy in accordance with the legal acts of the European Union and the national legal practice of the Member States are comprehended. The institutional structure of the EU anti-corruption bodies is analyzed.It is established that corruption in the EU countries is traditionally perceived as a serious national security issue and is viewed as an internal and external danger which may jeopardize the process of European integration. The EU’s anti-corruption policy has not only a legislative dimension. Conventions and agreements have been created that describe the general provisions for preventing and combating corruption in EU member states, and on the basis of this, national anti-corruption strategies are developed and special anti-corruption bodies are created.There is no separate regulatory document that would provide an exhaustive description of the legal framework for combating corruption in the European Union, nor is there a clearly defined list of binding international legal instruments. The European Union law has developed clear principles and approaches to fighting corruption.Fighting corruption remains a challenge at the European Union level. Alongside the introduction and application of preventive measures, it is crucial to strengthen police and judicial cooperation between Member States. It is important that Member States continue to work on implementing anti-corruption strategies. They should include a range of measures in both the preventive and repressive spheres. The proposals presented by the European Commission in the Communication of May 3, 2023 on the fight against corruption in the EU and around the world, which marked the beginning of the fifth, modern stage of the EU’s anti-corruption policy history, are aimed at achieving these perspectives. The ambitious document demonstrated the EU’s transition to more active and coordinated work in preventing and combating corruption at the internal and external levels.